PERLINDUNGAN HUKUM DAN BATASAN HAK IMUNITAS ADVOKAT DAN KURATOR - Sugiyatmo, Agus; Ratnawati, Elfrida (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
This research aims to analyze legal protection and limits on immunity rights for advocates and curators in Indonesia. This immunity right is given to ensure that both professions can carry out their duties and authorities effectively without the threat of groundless lawsuits. Legal protection for advocates in Indonesia is guaranteed by Law Number 18 of 2003 concerning Advocates. This law gives advocates the privilege of immunity in carrying out their professional duties. This protection includes protection from all civil and criminal cases as long as the advocates have acted in good faith and have no malicious intent. On the other hand, curators are protected by a different law – Law Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations – which only limits their responsibilities if they carry out their duties with professionalism and prudence. However, keep in mind that this protection does not cover everything as there are certain limitations that must be adhered to. Advocates and curators remain legally responsible if they are proven to have committed an error or intentional negligence. This research uses a normative-qualitative approach and comparative analysis to compare the legal system in Indonesia with other countries, as well as identifying challenges and best practices in protecting and monitoring immunity rights for advocates and curators. The research results show that effective legal protection must be balanced with strict monitoring mechanisms to prevent abuse of immunity rights and ensure the implementation of duties professionally and in accordance with the law.